Holding therapy: a harmful mental health intervention. Issue 2 (9th April 2013) - Mercer, Jean
Abstract Background Holding therapy, an alternative form of child psychotherapy, involves physical restraint and manipulation, and has been associated with adverse events. Objective To examine the evidence of effectiveness for holding therapy. Methods Four electronic databases were searched, as well as an ongoing hand search, to identify any studies reporting on the effectiveness of holding therapy. Results Eight studies were identified. All included studies claimed that holding therapy was efficacious, but none of the study designs were suitable for making such conclusions. Conclusion The evidence of effectiveness for holding therapy is insufficient, especially in the context of related adverse events.